Microstructure and erosion-corrosion behaviour of as-cast high chromium white irons containing molybdenum in aqueous sulfuric-acid slurry - S. Imurai (2018)
Microstructure and erosion-corrosion behaviour of as-cast high chromium white irons containing molybdenum in aqueous sulfuric-acid slurry was studied. The experimental irons contained 28 wt.%Cr with a Cr:C ratio of about 10 and up to 10 wt.%Mo. The irons with up to 6 wt.%Mo are hypoeutectic, whereas the iron with 10 wt.%Mo becomes eutectic/peritectic. Mo addition promotes formation of M23C6and M6C, instead of typical M7C3. Erosion-corrosion testing was performed in aqueous sulfuric-acid slurry containing alumina particles. The hypoeutectic Fe-28Cr-2.7C-1Mo with mainly M7C3and the eutectic/peritectic Fe-28Cr-2.6C-10Mo showed reduced wear rates of about 30% and 7% of that of the reference iron without Mo addition, respectively. The reduction of the carbide-matrix hardness difference, the increase of corrosion resistance of the matrices, and the increase of macro-hardness are determining factors for the improvement of erosion-corrosion resistance of the irons.